Toward Cubanness through Santeria: The Influence of Nostalgia as a Marketed Tool in the Protagonist of the Novel Dreaming in Cuban (1992) - Vázquez Pérez, Carlos David (Miscelánea: A Journal of English and American Studies, 2025)
Maya Socolovsky asserts that “the Cuban nation in García’s novels is a highly individualized and personal matter” (Socolovsky 2013: 133). This study, drawing on the description of nostalgia as a method “used to develop, sustain, and recreate individuals’ identities” (Sierra and McQuitty 2007: 100), conceptualizes Santeria as a nostalgic practice that enables the assertion of national identity (Cubanness). This literary analysis of an excerpt from Cristina García’s novel Dreaming in Cuban (1992) delves into Santeria’s role as a conduit for the protagonist Pilar to forge a tangible connection with her Cuban identity and traditions, even amidst her physical displacement from her homeland. Ultimately, this article attempts to demonstrate that, through the transformative power of the rituals and beliefs of this syncretic religion, Pilar rediscovers a deep feeling of rootedness towards her national and ethnic identity, a feeling that had previously evaded her during all her years as a Latina immigrant in the United States.